Book Review. Issue 3 (1st September 2017) - Fleet, Paul
The Aesthetics of Our Anger: Anarcho-Punk, Politics and Music, Mike Dines and Matthew Worley (2016)Colchester/New York/Port Watson: Minor Compositions, 322 pp., ISBN: 978-1-57027-318-6, pk, £18